Science and Technology Undergraduate Students' Use of the Internet, Cell Phones and Social Networking Sites to Access Library Information. - Lutishoor Salisbury; Jozef Laincz; Jeremy J. Smith (Issues in Science and Technology Librarianship)
Many academic libraries and publishers have developed mobile-optimized versions of their web sites and catalogs. Almost all database vendors and major journal publishers have provided a way to connect to their resources via the Internet and the mobile web. In light of this pervasive use of the Internet, mobile devices and social networking, this study examines the habits of 290 science and technology students (with majors in biology (51%), chemical engineering (15%), biological engineering (9%), kinesiology (5%), and animal science (4%)), to identify whether they use this technology for library-related activities. The primary objective of this study was to identify whether the students use the Internet, their cell phones, and/or social networking sites to access scholarly information available through the library. Specifically, we were interested in finding out: (1) how often students use the Internet and for what purposes; (2) what devices they use to access library information remotely; (3) for what purposes student use their cell-phones and whether they use them to access library resources, including our social networking sites; and (4) which social networking sites students use and for what purposes. Even though there are widespread uses of the Internet, cell phones, and social networking, this study found that the majority of the students surveyed do not readily identify them as a means to access library-provided databases, the library catalog or to retrieve full-text journal articles on demand or on the go. [ABSTRACT FROM AUTHOR]